Moderasi Beragama Dalam Ideologi Pancasila - Athoillah Islamy (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
It is undeniable that in the realm of praxis of religious and state life in Indonesia, there are still some people who clash Pancasila with religious teachings. Whereas as a state ideology, Pancasila actually contains the value of forming moderate religious understandings and attitudes for the benefit of life between religious people in Indonesia. This study intends to identify the dimensions of religious moderation values in the construction of Pancasila. This literature research uses a normative-philosophical approach. The results of the study concluded that there are dimensions of religious moderation values contained in the construction of Pancasila. First, the value of tolerance in the first precept is in the form of the value of forming paradigms and social attitudes of religion that prioritize pluralism in life between religious people. Second, the value of anti-radicalism in the second precept is in the form of the value of forming paradigms and social religious attitudes that prioritize the spirit of humanism. Third, the value of national commitment in the third precept is in the form of the value of forming paradigms and social attitudes of religion that uphold nationalism. Fourth, the accommodating value of local wisdom in the fourth and fifth precepts is in the form of the value of forming paradigms and social attitudes of diversity that prioritize the principle of deliberation and make the value of social justice in responding to various local wisdom. The theoretical implications of the findings of this study show that Pancasila contains universal values in the formation of a moderate social religious character in Indonesia. The limitation of this study is that it has not studied the role of the Indonesian government in disseminating the value of religious moderation contained in Pancasila in various lines of social life.